SAT0040 Safety, tolerability, pharmacokinetics and pharmacodynamics of bcd-089, novel monoclonal anti-il-6 receptor antibody: results from the first-in-human single dose escalation study in healthy volunteers. (12th June 2018) - Khlyabova, P.; Eremeeva, A.; Lutckii, A.; Dokukina, E.; Chernyaeva, E.; Ivanov, R.
Abstract : Background: BCD-089 is a fully human monoclonal antibody targeting membrane-bound and soluble forms of IL-6Rα, thereby blocking of IL-6 classic and trans- signalling. IL-6, a proinflammatory cytokine, plays a central role in the pathogenesis of many chronic inflammatory and autoimmune diseases. Thereby inhibition of IL-6 signalling is a promising approach in the treatment of immune-mediated pathology. Objectives: To assess safety, immunogenicity, pharmacokinetics and pharmacodynamics of a single administration of BCD-089. Methods: This was a phase I, open label, single ascending dose clinical study in healthy male volunteers, aged 22–37 years (n=19). In 1 st cohort, one «sentinel» volunteer received 0.006 mg/kg of BCD-089. Volunteers in cohorts 2–7 received single doses of BCD-089 0.3, 0.625, 1.0, 1.6, 2.2 and 2.9 mg/kg, respectively. Every next cohort was included after completed safety evaluation for the previous one. Safety, PK/PD and immunogenicity were assessed during 71 days follow up. Results: All enrolled subjects have completed follow up period of 71 days. No withdrawals occurred. Single SC administration of BCD-089 was well tolerated and showed good safety profile at all tested doses: no grade 3/4 AEs, SAEs, DLTs or allergic reactions were reported in any cohort. None of the volunteers developed ADA to BCD-089. The only AEs reported were grade 1 or 2 laboratory abnormalities. Single SC administration of BCD-089 had a dose-dependent PK: the drug became detectable in the serum within the first 12 hour after injection for all tested doses (2–8 hour for doses>1.0 mg/kg). Serum concentration dose-proportionally increased and reached maximum at day 3 after administration, then gradually decreased. Elimination half-life showed significant inter-personal variability and dose-dependency, reflecting non-linear PK typical for drugs with target-mediated disposition. The concentration of soluble IL-6 receptor increased after BCD-089 administration in a dose-dependent manner. A raise in the concentration of IL-6 was seen at doses>1.0 mg/kg. Membrane IL-6R saturation of 90%>100% was seen at doses≥0.6 mg/kg. Regardless to the dose, serum CRP decreased below the limit of detection in most volunteers within the first week after injection. All tested PD markers returned to baseline at the end of the follow-up. Conclusions: Single SC administration of BCD-089 was well tolerated, showed favourable safety profile and low immunogenicity at all tested doses in healthy volunteers. PK/PD assessment revealed non-linear PK and significant capacity to inhibit the IL-6 signalling pathway. These finding supports further clinical development of BCD-089. Disclosure of Interest: P. Khlyabova: None declared, A. Eremeeva Employee of: JSC BIOCAD, A. Lutckii Employee of: JSC BIOCAD, E. Dokukina Employee of: JSC BIOCAD, E. Chernyaeva Employee of: JSC BIOCAD, R. Ivanov Employee of: JSC BIOCAD